2019
DOI: 10.1371/journal.pone.0212053
|View full text |Cite
|
Sign up to set email alerts
|

SLFN11 can sensitize tumor cells towards IFN-γ-mediated T cell killing

Abstract: Experimental and clinical observations have highlighted the role of cytotoxic T cells in human tumor control. However, the parameters that control tumor cell sensitivity to T cell attack remain incompletely understood. To identify modulators of tumor cell sensitivity to T cell effector mechanisms, we performed a whole genome haploid screen in HAP1 cells. Selection of tumor cells by exposure to tumor-specific T cells identified components of the interferon-γ (IFN-γ) receptor (IFNGR) signaling pathway, and tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 29 publications
(41 reference statements)
1
28
0
Order By: Relevance
“…In addition, chemotherapy resistance mechanisms associated with the frequently observed loss of Schlafen11 (SLFN11) expression could be restored by EZH2 inhibition ( Gardner et al., 2017 ), although this was not observed in a set of SCLC PDX models ( Drapkin et al., 2018 ). However, it might require a functional immune system to benefit from SLFN11 expression ( Mezzadra et al., 2019 ). Promising progress is being made with immunotherapy strategies showing a durable response in a small subset of patients ( Hellmann et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chemotherapy resistance mechanisms associated with the frequently observed loss of Schlafen11 (SLFN11) expression could be restored by EZH2 inhibition ( Gardner et al., 2017 ), although this was not observed in a set of SCLC PDX models ( Drapkin et al., 2018 ). However, it might require a functional immune system to benefit from SLFN11 expression ( Mezzadra et al., 2019 ). Promising progress is being made with immunotherapy strategies showing a durable response in a small subset of patients ( Hellmann et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…During infection, cancer and autoimmunity, antigen presentation is enhanced by locally produced cytokines including IFN-γ. The IFN-γ signaling pathway is intact in HAP1 cells(26). Our experiments now showed that induction of IFN-γ signaling upregulates HLA-I mRNA and surface protein levels (Figure 2E and F).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to normal adrenal gland tissues, all the three genes showed a reduced expression in NBL, mainly SLFN12 (Figure ). No genetic diseases have been associated with germline mutations in neither SLFN11 , SLFN12 or SLNF13 , but they are believed to regulate cell growth, to promote cell differentiation, to inhibit migration and invasion, to play a role in DNA repair …”
Section: Resultsmentioning
confidence: 99%
“…No genetic diseases have been associated with germline mutations in neither SLFN11, SLFN12 or SLNF13, but they are believed to regulate cell growth, to promote cell differentiation, to inhibit migration and invasion, to play a role in DNA repair. [9][10][11][12] In Pt-40, a duplication of the SOX4 was identified. This gene encodes for a transcription factor, which is markedly overexpressed in NBL (Figure 1), as well as in many types of cancer conferring poor prognosis.…”
Section: Genetic Findingsmentioning
confidence: 99%